Postprandial Hypertriglyceridaemia Revisited in the Era of Non-Fasting Lipid Profile Testing: A 2019 Expert Panel Statement, Main Text - Kolovou, Genovefa D.; Watts, Gerald F.; Mikhailidis, Dimitri P.; Pérez-Martínez, Pablo; Mora, Samia; Bilianou, Helen; Panotopoulos, George; Katsiki, Niki; Ooi, Teik C.; Lopez-Miranda, José; Tybjærg-Hansen, Anne; Tentolouris, Nicholas; et al. (Current Vascular Pharmacology, 2019)
Residual vascular risk exists despite the aggressive lowering of Low-Density Lipoprotein Cholesterol (LDL-C). A contributor to this residual risk may be elevated fasting, or non-fasting, levels of Triglyceride (TG)-rich lipoproteins. Therefore, there is a need to establish whethe a standardised Oral Fat Tolerance Test (OFTT) can improve atherosclerotic Cardiovascular (CV) Disease (ASCVD) risk prediction in addition to a fasting or non-fasting lipid profile. An expert panel considered the role of postprandial hypertriglyceridaemia (as represented by an OFTT) in predicting ASCVD. The panel updated its 2011 statement by considering new studies and various patient categories. The recommendations are based on expert opinion since no strict endpoint trials have been performed. Individuals with fasting TG concentration <1 mmol/L (89 mg/dL) commonly do not have an abnormal response to an OFTT. In contrast, those with fasting TG concentration ≥2 mmol/L (175 mg/dL) or nonfasting ≥2.3 mmol/L (200 mg/dL) will usually have an abnormal response. We recommend considering postprandial hypertriglyceridaemia testing when fasting TG concentrations and non-fasting TG concentrations are 1-2 mmol/L (89-175 mg/dL) and 1.3-2.3 mmol/L (115-200 mg/dL), respectively as an additional investigation for metabolic risk prediction along with other risk factors (obesity, current tobacco abuse, metabolic syndrome, hypertension, and diabetes mellitus). The panel proposes that an abnormal TG response to an OFTT (consisting of 75 g fat, 25 g carbohydrate and 10 g proteins) is >2.5 mmol/L (220 mg/dL). Postprandial hypertriglyceridaemia is an emerging factor that may contribute to residual CV risk. This possibility requires further research. A standardised OFTT will allow comparisons between investigational studies. We acknowledge that the OFTT will be mainly used for research to further clarify the role of TG in relation to CV risk. For routine practice, there is a considerable support for the use of a single non-fasting sample.
Keywords: atherosclerotic cardiovascular disease